2022
DOI: 10.1111/ane.13673
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of circulating miRNAs in Duchenne disease: Association with muscle injury and metabolic parameters

Abstract: This study aimed to evaluate whether the expression of circulating dys-tromiRs and a group of oxidative stress-related (OS-R) miRNAs is associated with muscle injury and circulating metabolic parameters in Duchenne muscular dystrophy (DMD) patients. Methods: Twenty-four DMD patients were included in this cross-sectional study. Clinical scales to evaluate muscle injury (Vignos, GMFCS, Brooke, and Medical Research Council), enzymatic muscle injury parameters (CPK, ALT, and AST), anthropometry, metabolic indicato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Meanwhile, there several factors would affect the level of ALT. Studies have reported that the ALT level may be varied with body mass index, abnormal lipid and carbohydrate metabolism, and the time of the day [27,28]. Thus, we need to pay attention to these factors while evaluating the HBV DNA level of HBeAg (−) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, there several factors would affect the level of ALT. Studies have reported that the ALT level may be varied with body mass index, abnormal lipid and carbohydrate metabolism, and the time of the day [27,28]. Thus, we need to pay attention to these factors while evaluating the HBV DNA level of HBeAg (−) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle injury was evaluated in terms of function and strength using clinical scales [ 11 , 18 ] and quantifying circulating markers of muscle injury. The muscle function of the lower limbs was graded using the Vignos scale [ 19 ] and the Gross Motor Function Classification System (GMFCS) [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Regarding EV-derived miRNAs, miR-133a-3p was increased while miR-29c-3p was decreased in patients with DMD compared with healthy individuals. Almeida-Becerril et al [ 95 ] compared the levels of several miRNAs between ambulant and non-ambulant patients with DMD. They found that miR-133a-3p, miR-206, miR-21-5p, miR-31-5p, miR-128-3p, and miR-144-3p levels were higher in the ambulant group.…”
Section: Microrna Alterations In Duchenne Muscular Dystrophymentioning
confidence: 99%